Tinjauan Green Economy dalam Hukum Persaingan Usaha di Indonesia - Muhammad Pravest Hamidi; Muhammad Anas Fadli; Yonathan Wiryajaya Wilion (Jurnal Persaingan Usaha, 2022)
Green Economy is a medium that can reduce the adverse effects of climate change. However, the implementation of the Green Economy sometimes encounters obstacles in the prohibition of unfair business competition and monopolistic practices. In fact, the legal aspects of business competition can promote and accelerate the implementation of the Green Economy. The researcher analyzed the concept of Green Economy, Rule of Reason, and various cases such as “Washing Machine” and “Chicken for Tomorrow” to support this research. The results obtained by the researchers are: (1) environmental aspects have not been explicitly recognized in business competition law in Indonesia but can be interpreted as being included in the phrase "public interest" (2) the inclusion of explanations regarding environmental aspects can create legal certainty and legal benefits for business owners and society, (3) in applying concessions for the sake of the environment, as long as it makes a "significant" contribution to the environment, concessions should still be given even though it is detrimental to consumers in a cost-benefit analysis. Thus, Indonesia needs to firmly recognize the environmental aspects of business competition law in Indonesia to accelerate the implementation of the Green Economy. Keywords: Green Economy; Public Interest; Sustainable Agreement